2007
DOI: 10.1021/bi062291f
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of a DNA Dodecamer Duplex with and without a Cisplatin 1,2-d(GG) Intrastrand Cross-Link:  Comparison with the Same DNA Duplex Containing an Oxaliplatin 1,2-d(GG) Intrastrand Cross-Link,

Abstract: Proteins that discriminate between cisplatin-DNA adducts and oxaliplatin-DNA adducts are thought to be responsible for the differences in tumor range, toxicity, and mutagenicity of these two important chemotherapeutic agents. However, the structural basis for differential protein recognition of these adducts has not been determined and could be important for the design of more effective platinum anticancer agents. We have determined high-resolution NMR structures for cisplatin-GG and undamaged DNA dodecamers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(155 citation statements)
references
References 49 publications
7
147
1
Order By: Relevance
“…Our structures of the CP-and OX-GG adducts in the AGGC sequence context (17,18) were the first of Pt-GG adducts with a purine on the 5′ side of the adduct, and we did not observe a large positive slide and shift at the A5-G6 base-pair step of those adducts. Furthermore, for the T5-G6 base-pair step of the OX-TGGT adduct we observed a large positive slide, but a slightly negative shift.…”
Section: Dna Helical Parameters Common To All Pt-gg Adductsmentioning
confidence: 58%
See 2 more Smart Citations
“…Our structures of the CP-and OX-GG adducts in the AGGC sequence context (17,18) were the first of Pt-GG adducts with a purine on the 5′ side of the adduct, and we did not observe a large positive slide and shift at the A5-G6 base-pair step of those adducts. Furthermore, for the T5-G6 base-pair step of the OX-TGGT adduct we observed a large positive slide, but a slightly negative shift.…”
Section: Dna Helical Parameters Common To All Pt-gg Adductsmentioning
confidence: 58%
“…Previous studies in our laboratory (17,18) (manuscript in preparation) and other laboratories (17)(18)(19)(20) have shown that imino proton resonance of the 5′G of a Pt-GG adduct is more solvent accessible than that of the 3′G. This data suggests that the DNA may be more distorted and/or flexible on the 5′ side of the adduct.…”
Section: Conformational Flexibility On the 5′ Side Of The Adductmentioning
confidence: 73%
See 1 more Smart Citation
“…The following contacts observed in the NMR study are not seen in the x-ray structure of oxaliplatin-DNA: (i) hydrogen-bond contacts between 5'-NH 2 hydrogen of DACH with g6 phosphate backbone oxygen atom (H---O: 1.879 Å); and (ii) contacts between 3'-NH 2 and O4 atom of T8 (H---O: 2.849 Å) [18].…”
Section: Molecular Dynamics Studies On Platinum-dna Adductsmentioning
confidence: 85%
“…Platinum-DNA oligonucleotide adducts have been studied using crystallography [14][15][16], NMR [17,18], and computational approaches [19][20][21]. Crystallographic studies have previously been carried out on 12-mer DNA oligonucleotide adducts of cisplatin, oxaliplatin and JM118 (JM118 is the active metabolite of Satraplatin) by Lippard and coworkers [14][15][16].…”
Section: Molecular Dynamics Studies On Platinum-dna Adductsmentioning
confidence: 99%